(untitled) (Medico Legal Update, 2021)
Background: Special Economic Zone (SEZ) policy of Thai government aimed to promote the economy in bordered provinces. Its establishment may cause concerns and impacts on communities. This article explores those issues arising from SEZ establishment in Southern Thailand. Method: The scoping step of rapid health impact assessment process was applied using documentary research combined with qualitative descriptive approaches, including focus group discussions, interviews, and brainstorming. Data were collected from seventy participants, comprising government officials, local government officials, community leaders, public health volunteers, members of local organizations, and local residents. Content analysis was used to analyze the data. Conclusion: The most important issues were found in four aspects—economic, social, environmental, and health. The economic aspect involved higher income and more employment opportunities, while for the environmental aspect, the issues were related to waste management and water pollution. The social issues comprised the build-up of traffic and the influx of migrant workers. The health issues were emerging/reemerging infectious diseases, particularly from migrant workers and the insufficiency of health services. As a result, a rapid health impact assessment should be carried out based on these issues. It should be taken into consideration by local officials responsible for developing and regulating the SEZ.